Tingkat Pengetahuan Dan Sikap Pelajar Di Smk Kerabat Kita Bumiayu Mengenai Kasus Penyalahgunaan Obat Dengan Metode Peer Education Sebagai Upaya Apoteker Dalam Promosi Kesehatan - Radesty Citra Agmalia; Peppy Octaviani DM; Sunarti Sunarti (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Drug abuse is estimated to affect 35 million people globally and requires treatment. Seeing the magnitude of the influence of group membership for adolescents, a health promotion strategy with the right method is needed, so that the information received can increase students' knowledge and attitudes regarding drug abuse cases. The purpose of this study was to determine the effect of the peer education method on the level of knowledge and attitudes of students regarding drug abuse cases. This type of research is descriptive with a cross sectional approach. The population in this study are students SMK Kerabat Kita Bumiayu. The research sample was 94 respondents. The research instrument used was a questionnaire. Conclusions based on univariate analysis, the majority of students there are 68 male (72.3%), female students 26 (27.7%) and students living with parents 54 (57.4%) the status of living in boarding houses is 37 (39.4%) and the status of living with parents is 3 (3.2%). The results showed that the peer education method had an effect on students' knowledge and attitudes regarding drug abuse cases (P = 0.0000). In conclusion, there is an influence of the peer education method on the knowledge and attitudes of students at SMK Kerabat Kita Bumiayu.